Immune evasion of Borrelia miyamotoi: CbiA, a novel outer surface protein exhibiting complement binding and inactivating properties - Röttgerding, Florian; Kirschfink, Michael; Wallich, Reinhard (Scientific reports, 2017)
Borrelia (B.) miyamotoi, an emerging tick-borne relapsing fever spirochete, resists complement-mediated killing. To decipher the molecular principles of immune evasion, we sought to identify determinants contributing to complement resistance. Employing bioinformatics, we identified a gene encoding for a putative Factor H-binding protein, termed CbiA (complement binding and inhibitory protein A). Functional analyses revealed that CbiA interacted with complement regulator Factor H (FH), C3, C3b, C4b, C5, and C9. Upon binding to CbiA, FH retained its cofactor activity for Factor I-mediated inactivation of C3b. The Factor H-binding site within CbiA was mapped to domain 20 whereby the C-terminus of CbiA was involved in FH binding. Additionally, CbiA directly inhibited the activation of the classical pathway and the assembly of the terminal complement complex. Of importance, CbiA displayed inhibitory activity when ectopically produced in serum-sensitive B. garinii G1, rendering this surrogate strain resistant to human serum. In addition, long-term in vitro cultivation lead to an incremental loss of the cbiA gene accompanied by an increase in serum susceptibility. In conclusion, our data revealed a dual strategy of B. miyamotoi to efficiently evade complement via CbiA, which possesses complement binding and inhibitory activities.
Gesehen am 16.08.2018